Pengelolaan Sampah oleh Masyarakat Perkotaan di Kota Yogyakarta - Vidyana Arsanti; Sri Rum Giyarsih (Teknik Lingkungan Universitas Islam Indonesia, 2012)
Garbage is one of urgent problems in urban area. The lack of idle lands in urban area make garbage problems more difficult. This research is conducted in Yogyakarta City that has been done the garbage management successfully.Objective of the research is to describe and classify the garbage management models implemented by the society. This research uses survey methods that is encode the region where the garbage management is implemented, with the direct interview to respondents and questionnaire as a means of data collecting. The descriptive analysis is applied in this research.The research shows that garbage management activity that has been applied in some locations is good enough by developing three model of garbage management. This research also suggests networking among government, society figure, and urban society to reach the best garbage management.